EXTRACT OF MORINGA LEAF AND SEAWEED AS BIOSTIMULANT FOR INCREASING SUCCESS AND GROWTH OF COCOA (Theobroma cacao L.) SHOOT GRAFTING - Ramdani, Muhammad Rizki; Evizal, Rusdi; Wibowo, Lestari; Ramadiana, Sri (JURNAL AGROTROPIKA, 2025)
Cocoa (Theobroma cacao L.) is a plantation crop that contributes to Indonesia’s economy through export value and serves as the main source of income for farmers in major production centers. Grafting technology is widely used to increase productivity; however, its success rate remains low. The use of biostimulants derived from moringa leaf extract and seaweed extract offers an alternative solution to improve the success and growth of cocoa grafts. This study aimed to determine the effect of type and concentration of biostimulants on the success and growth of cocoa grafts. The research was conducted from December 2024 to February 2025 in Labuhan Dalam, Tanjung Senang District, Bandar Lampung City. A non-factorial randomized complete block design (RCBD) was used, consisting of 7 treatments and 3 replications. The treatments included a control (0 ml/l), moringa leaf extract at 150 ml/l, 300 ml/l, and 450 ml/l, as well as seaweed extract at 150 ml/l, 300 ml/l, and 450 ml/l. Data were analyzed using ANOVA and tested with the Least Significant Difference (LSD) at a 5% significance level. The results showed that the application of biostimulants had a significant effect on the time of shoot emergence, number of shoots, shoot length, shoot diameter, and leaf greenness. However, the treatments did not significantly affect the number of leaves, number of flushes, fresh weight of shoots, or dry weight of shoots. All biostimulant applications resulted in a 100% grafting success rate. The best concentration of both moringa leaf and seaweed biostimulant extracts was 300 ml/l. Key words: Biostimulants, moringa leaves, seaweed, shoot grafting